High Prevalence of Epilepsy in an Onchocerciasis-Endemic Area in Mvolo County, South Sudan: A Door-To-Door Survey - Raimon, Stephen; Dusabimana, Alfred; Abd-Elfarag, Gasim; Okaro, Samuel; Carter, Jane Y.; Newton, Charles R.; Logora, Makoy Yibi; Colebunders, Robert (MDPI)
In June 2020, a door-to-door household survey was conducted in Mvolo County, an onchocerciasis-endemic area in South Sudan. A total of 2357 households containing 15,699 individuals agreed to participate in the study. Of these, 5046 (32.1%, 95% CI: 31.4-32.9%) had skin itching and 445 (2.8%, 95% CI: 2.6-3.1%) were blind. An epilepsy screening questionnaire identified 813 (5.1%) persons suspected of having epilepsy. Of them, 804 (98.9%) were seen by a medical doctor, and in 798 (98.1%) the diagnosis of epilepsy was confirmed. The overall epilepsy prevalence was 50.8/1000 (95% CI: 47.6-54.4/1000), while the prevalence of nodding syndrome was 22.4/1000 (95% CI: 20.1-24.9/1000). Younger age, being male, skin itching, blindness, and living in a neighbourhood or village close to the Naam River were risk factors for epilepsy. The annual incidence of epilepsy was 82.8/100,000 (95% CI: 44.1-141.6/100,000). Among children 7-9 years old without epilepsy, 34% were Ov16 seropositive, suggesting high ongoing Onchocerca volvulus transmission, but only 41.9% of them took ivermectin during the last mass distribution. In conclusion, a high prevalence and incidence of epilepsy was observed in Mvolo, South Sudan. Strengthening of the onchocerciasis elimination programme is urgently needed in order to prevent epilepsy in this region.
t: © 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).
Keywords: Onchocerca volvulus; Epilepsy; Ivermectin; Nodding syndrome; Onchocerciasis; Prevalence